2003
DOI: 10.1007/s00125-003-1064-1
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated viral vector-mediated human vascular endothelial growth factor gene transfer stimulates angiogenesis and wound healing in the genetically diabetic mouse

Abstract: Aims/hypothesis. We studied the gene therapy efficacy of diabetes-associated wound healing disorder with an adeno-associated virus (AAV) vector expressing the 165-amino acid isoform of human vascular endothelial growth factor-A (VEGF-A) by using an incisional skin-wound model produced on the back of female diabetic C57BL/KsJ db+/db+ mice and their normal littermates (db+/+m). Methods. Animals were randomized to receive intradermally into the wound edges either rAAV-LacZ (a control gene), or rAAV-VEGF165. Anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
118
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 48 publications
2
118
0
1
Order By: Relevance
“…Therefore, restoring structural and functional microvasculature by supplementary delivery of VEGF-A or Ang1 could be beneficial to promote wound healing in diabetes. In fact, recent reports (12,13) indicate that topical application of VEGF-A promotes cutaneous wound healing through increased angiogenesis and by mobilizing and recruiting bone marrow-derived cells. However, exogenous VEGF-A often results in leaky, inflamed, and malformed vessels, greatly compromising its therapeutic utility (12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, restoring structural and functional microvasculature by supplementary delivery of VEGF-A or Ang1 could be beneficial to promote wound healing in diabetes. In fact, recent reports (12,13) indicate that topical application of VEGF-A promotes cutaneous wound healing through increased angiogenesis and by mobilizing and recruiting bone marrow-derived cells. However, exogenous VEGF-A often results in leaky, inflamed, and malformed vessels, greatly compromising its therapeutic utility (12)(13)(14).…”
mentioning
confidence: 99%
“…In fact, recent reports (12,13) indicate that topical application of VEGF-A promotes cutaneous wound healing through increased angiogenesis and by mobilizing and recruiting bone marrow-derived cells. However, exogenous VEGF-A often results in leaky, inflamed, and malformed vessels, greatly compromising its therapeutic utility (12)(13)(14). In comparison, Ang1 is a specific growth factor functioning to generate a stable and functional vasculature through Tie2 and Tie1 receptors (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…It is not surprising then, that many studies have found angiogenesis to be beneficial for wound repair. Stimulation of angiogenesis can enhance healing rates, [27][28][29][30][31][32][33] whereas a reduction in angiogenesis can impair the same. [34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of angiogenesis can enhance healing rates, [27][28][29][30][31][32][33] whereas a reduction in angiogenesis can impair the same. [34][35][36][37] The benefits of enhanced angiogenesis have primarily been shown in models of impaired wound healing 28,32,33 or severe injury. [29][30][31] In contrast, several reports have shown that modulation of angiogenesis does not affect epidermal healing rates or overall wound closure to a great degree, [38][39][40][41][42][43] and some studies have even reported enhanced healing with reduced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be noted that adenoviral overexpression of VEGF isoforms (VEGF121 and VEGF165) or topical treatment with VEGF does accelerate wound healing, enhances wound vascularity and increases bursting strength of wounds in mice and rats. [31][32][33][34][35] The overall small impact of antiangiogenic therapy on wound healing may result from the fact that wound healing is a complex coordinated process encompassing a variety of different cell types (keratinocytes, endothelial cells, fibroblasts, inflammatory cells, epidermal cells) and growth factors other than VEGF such as basic fibroblast growth factor (bFGF), epidermal growth factor (EGF), keratinocyte growth factor (KGF). Thus, despite an impairment of wound angiogenesis, redundant mechanisms not further analyzed in this study appear to prevent a gross delay in wound closure.…”
Section: Discussionmentioning
confidence: 99%